The larva of Perissolestes remotus (Williamson & Williamson, 1924) (Zygoptera: Perilestidae) - Román Heracleo, Jareth (2018)
The larva of Perissolestes remotus is described for the first time based on Costa Rican specimens collected in forested streams with abundant organic matter. It is characterized by a slender, elongated body, with lateral keels on abdominal segments 1–9, and a middorsal row of spines on segments 4–10. We also provide additional notes on the larvae of P. magdalenae using material from Panama. The larva is similar to the only other species of Perissolestes present in Mexico and Central America, P. magdalenae, but can be separated by the articulation of the prementum-postmentum reaching the metacoxa (reaching the mesocoxa in P. magdalenae) and the female gonapophyses exceeding past the posterior margin of S10 (just reaching posterior margin in P. magdalenae). At the generic level, Perissolestes can be differentiated from Perilestes by the presence of abdominal keels on segments 1–9 (from 4–9 in Perilestes) and by having caudal gills with small spines along the medial trachea (spines absent in Perilestes).